An integrated approach for enhancing data security - Manikandan, G; Jeeva Dharani, R; Maya, R (International Journal of Engineering and Technology, 2018)
Information security is a key challenge in todayâ€™s information era where a huge volume of data is being generated on the internet as a result of the online transaction. This data needs to be protected from the unauthorized users on the web. Cryptography is used to ensure the confidentiality and integrity of data in the virtual world. The strength of the cryptographic algorithm relies on the complexity involved in retrieving the original content from the unintelligible information. The system proposed in this paper focuses on the use of a different mechanism to increase complexity involved in the cryptanalysis. Different cryptographic techniques are used to create a modified plain text and modified key. The newly generated key is used to encrypt the modified plaintext to generate the ciphertext. From the security analysis, it is evident that the time taken for cryptanalysis by the proposed scheme is more when compared with the existing systems. Â Â